SOC 211: Introduction to Sociology: Project Description - Wortham, Carol (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The two projects you must complete for this course are designed to make you conscious of what it means to act as a sociologist. The projects are also aimed at personal growth. They are not to be term papers, but are to be brief reports of around 4 to 5 pages. The projects must be typed, double-spaced on one side of the paper only. Neatness and proper grammar are assumed expectations. These projects must be submitted on due date or five points will be deducted for each late day. This includes Monday through Friday.